Apprenticeship and Guided Participation” in University English Language Teaching - Perera, M.E.S. (My University, 2006)
According to socio-cultural theory and activity theory, children learn through participating learned English in a friendly and relaxed environment with opportuniti with others in common purposeful activities. Two basic, interrelated concepts in this theory are apprenticeship and guided participation. Based on these concepts, this paper analyses an experimental. Teaching/learning Situation which a group of postgraduate students developed and conducted a language- proficiency course unit for undergraduates. Analysis of post course evaluation indicated that the experiment was successful. Undergraduates learned English in a friendly and relaxed environement with opportunities for oral interaction while the postgraduate students had an opportunity to put into practice what they were learning. Thus , through apprenticeship and guided participation both groups benefitted. The effect of western colonization on ‘school cultures’ and its impact on learning and teaching English. Paper presented at the 10th international conference on Sri Lanka Studies. 16th -18th December 2005. University of Kelaniya, Sri Lanka Making Teacher Education interactive – University of Colombo experience. Joint presentation with Prof. S. Wijetunge. South Asian Consortium for Teacher Education and Development (SACTED) theme seminar,20 th May 2005.Colombo Learning the second language in a disadvantaged school setting: Is ‘learned helplessness’ – a cause for failure to learn the second language? Paper presented at the conference on Sri Lanka; Challenges of a society in transition. 16 – 18 December 2004. Faculty of Graduate Studies, University of Colombo.